Student Opinions on the Use of High-Tech Mobile Devices in the Design of Digital Games for Learning - Jeanette, Eva; Ovchinnikova, Brooks; Nurdiyanto, Heri (International Journal of Artificial Intelligence Research, 2022)
Schools have adopted digital technologies as a strategy for learning and teaching activities because it offers opportunities for scaffolding. This strategy has been implemented in conjunction with creative activities. In addition, activities based on digital games, known as digital game-based learning (DGBL), and various mobile technologies, have been piloted in schools over the past few years to develop innovative learning. The purpose of this research is to investigate how children's collaborative interactions develop while participating in activities requiring them to solve problems utilizing intelligent and mobile technology. Our research combines theoretical viewpoints on joint participation, affordances, and a sense of community in the context of collaborative interactions. This is done with a contextual perspective on learning as its starting point. The following are some of the questions posed in this research: (1) How do children's digital game design activities drive and support collaborative interactions while they are engaged in problem-solving activities? Furthermore, (2) How do children's ideas for designing digital games manifest themselves during activities involving the design of games that involve innovative mobile technology? The study is based on a case where a creative workshop was held with 22 Swedish third-grade children aged 9 to 10 years old who participated in game design activities in a pedagogical lab. When the children worked together to solve the problem of designing and producing a joint digital game idea using mobile technology, a sense of community emerged due to their efforts. The study's results were analyzed using a thematic approach, which revealed that the children used different orientations in their collaborative interactions. Based on this, we argue that it is crucial to be aware of the pedagogical context when preparing for educational activities that involve innovative mobile technology. This is because the pedagogical context is the aspect of the design that creates meaningful collaborative interactions, and it is only then that innovative mobile technology becomes smart. These findings have significant ramifications for the methodological field of incorporating cutting-edge mobile technology into various types of educational settings